Family First: Evidence of Consistency and Variation in the Value of Family Versus Personal Happiness Across 49 Different Cultures. (May 2023) - Krys, Kuba; Chun Yeung, June; Haas, Brian W.; van Osch, Yvette; Kosiarczyk, Aleksandra; Kocimska-Zych, Agata; Torres, Claudio; Selim, Heyla A.; Zelenski, John M.; Bond, Michael Harris; Park, Joonha; Lun, Vivian Miu-Chi; et al.
People care about their own well-being and about the well-being of their families. It is currently, however, unknown how much people tend to value their own versus their family's well-being. A recent study documented that people value family happiness over personal happiness across four cultures. In this study, we sought to replicate this finding across a larger sample size ( N = 12, 819) and a greater number of countries ( N = 49). We found that the strength of the idealization of family over personal happiness preference was small (average Cohen's d s = .20, range −.02 to.48), but present in 98% of the studied countries, with statistical significance in 73% to 75%, and variance across countries <2%. We also found that the size of this effect did vary somewhat across cultural contexts. In Latin American cultures highest on relational mobility, the idealization of family over personal happiness was very small (average Cohen's d s for Latin America = .15 and .18), while in Confucian Asia cultures lowest on relational mobility, this effect was closer to medium ( d s > .40 and .30). Importantly, we did not find strong support for traditional theories in cross-cultural psychology that associate collectivism with greater prioritization of the family versus the individual; country-level individualism–collectivism was not associated with variation in the idealization of family versus individual happiness. Our findings indicate that no matter how much various populists abuse the argument of "protecting family life" to disrupt emancipation, family happiness seems to be a pan-culturally phenomenon. Family well-being is a key ingredient of social fabric across the world, and should be acknowledged by psychology and well-being researchers and by progressive movements too.